Risk assessment and support optimization for cable trench construction in soft soil areas in Zhejiang province - Linlin Zhang; Rong Bian; Keji Chen; Guoqiang Li; Miaosong Gu (Discover Applied Sciences)
Abstract The construction of underground structures such as cable trenches in soft soil areas presents unique challenges due to the high compressibility, low strength, and variability of the soil. As a critical component of urban infrastructure, the stability and safety of cable trenches are directly related to the reliability of power supply and the secure operation of the city. This study establishes a two-dimensional finite element numerical model of a cable trench to investigate the influence of different support methods and parameters on the overall and local geotechnical characteristics of the surrounding strata. A parametric sensitivity analysis is conducted to explore the response patterns of support structures under varying geological and environmental conditions, clarifying the evolution of soil parameters and comprehensive risk assessment indicators around the trench. The results indicate that steel sheet piles are more effective than timber piles in suppressing base heave. The increase in surface surcharge may help reduce overall base heave, leading to an increase in relative uplift at the trench base. The distance and weight of existing buildings significantly affect the magnitude of base heave, while a lowered groundwater table results in increased base heave and lateral displacement. Moreover, stratigraphic configurations with soft soil overlying hard strata are more favorable for trench stability than the reverse, suggesting that weak underlying layers elevate the risk of trench failure. In such cases, the presence of nearby buildings further amplifies this risk. These findings offer valuable insights for the design and construction of cable trenches in soft soil regions.